1993
DOI: 10.1084/jem.177.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus and Hodgkin's disease: transcriptional analysis of virus latency in the malignant cells.

Abstract: Here we extend preliminary results on viral gene expression in HRS cells by adopting polymerase chain reaction-based and in situ hybridization assays capable of detecting specific EBV latent transcripts diagnostic of the different possible forms of EBV latency. We show that the transcriptional program of the virus in HRS cells is similar to that seen in NPC in several respects: (a) selective expression of EBNA1 mRNA from the BamHI F promoter; (b) downregulation of the BamHI C and W promoters and their associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
151
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(158 citation statements)
references
References 53 publications
6
151
0
1
Order By: Relevance
“…29 However no mRNA coding for EBNA-5 has been detected in RS cells by in situ hybridization studies. 30 Another study found an interaction between EBV-encoded EBNA-1 protein, which is expressed in all EBV-infected cells, and p53 protein. 31 In our study we found no relation between the level of p53 protein expression and the presence of EBV infection.…”
Section: Discussionmentioning
confidence: 98%
“…29 However no mRNA coding for EBNA-5 has been detected in RS cells by in situ hybridization studies. 30 Another study found an interaction between EBV-encoded EBNA-1 protein, which is expressed in all EBV-infected cells, and p53 protein. 31 In our study we found no relation between the level of p53 protein expression and the presence of EBV infection.…”
Section: Discussionmentioning
confidence: 98%
“…In latency type I, which is found in Burkitt's lymphoma [23], EBV nuclear antigen (EBNA)-1 and BamHI A rightward fragments (BARTs) are expressed in addition to EBERs (Table 1). In latency type II, characteristics of Hodgkin's lymphoma [24] and nasopharyngeal carcinoma [25], EBNA-1, latent membrane protein (LMP)-1, LMP-2, BARTs, and EBERs are expressed (Table 1). In latency type III, associated with lymphoproliferative disorders [26], all latency genes, including EBNA-2 and EBNA-3s, are expressed ( Table 1).…”
Section: Classification Of Ebv-associated Diseases By Ebv Latent Genesmentioning
confidence: 99%
“…In latency II, as noted in EBV-associated Hodgkin's disease and nasopharyngeal carcinoma, the EBNA-1, LMP-1 and LMP-2 genes but not other EBNA genes are transcribed (Brooks et al, 1992;Deacon et al, 1993). In latency I, EBV-infected cells express only EBNA-1, which is essential for episomal replication.…”
mentioning
confidence: 99%